2007
DOI: 10.5194/acp-7-697-2007
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the <sup>222</sup>Rn family turbulent transport in the convective atmospheric boundary layer

Abstract: Abstract. The combined effect of turbulent transport and radioactive decay on the distribution of 222 Rn and its progeny in convective atmospheric boundary layers (CBL) is investigated. Large eddy simulation is used to simulate their dispersion in steady state CBL and in unsteady conditions represented by the growth of a CBL within a pre-existing reservoir layer.The exact decomposition of the concentration and flux budget equations under steady state conditions allowed us to determine which processes are respo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 68 publications
2
9
0
Order By: Relevance
“…Narrow vigorous thermals surrounded by relatively large subsidence motions generate turbulent mixing leading to a so-called mixed layer where, for instance, potential temperature is nearly constant with height. During the morning transition and the development of the unstable boundary layer, we find results similar to Vinuesa and Galmarini (2007). The concentration of all radio nuclei reduces abruptly in spite of the fresh emission of S 0 .…”
Section: Diurnal Evolution Of 222 Rn and Its Progeny Concentrations Dsupporting
confidence: 75%
See 2 more Smart Citations
“…Narrow vigorous thermals surrounded by relatively large subsidence motions generate turbulent mixing leading to a so-called mixed layer where, for instance, potential temperature is nearly constant with height. During the morning transition and the development of the unstable boundary layer, we find results similar to Vinuesa and Galmarini (2007). The concentration of all radio nuclei reduces abruptly in spite of the fresh emission of S 0 .…”
Section: Diurnal Evolution Of 222 Rn and Its Progeny Concentrations Dsupporting
confidence: 75%
“…They showed that the turbulent properties of atmospheric convective boundary layers are of importance to study the dispersion and the transport of the 222 Rn family. In this present study, we broaden the recent work of Vinuesa and Galmarini (2007) by extending the study of the control exerted by turbulence on 222 Rn and its progeny atmospheric dispersion to the full range of stabilities characterizing atmospheric boundary layers. Not only do we corroborate their findings for the unsteady convective boundary layer but we generalize and complete the study by simulating a realistic diurnal cycle consisting of the three stability regimes i.e.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Radon can then be used to compute an equivalent mixing height throughout the night. Then, after sunrise and the resumption of buoyancy-driven turbulent mixing, equivalent mixing height and actual mixing height become comparable for a while because the assumption of a wellmixed boundary layer becomes valid Vinuesa and Galmarini, 2007). For a period during the morning transition, the mixing layer can be observed with both lidar and radon.…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 87%
“…Also none of the contributions shows a peak at the top of the boundary layer, and second, buoyancy is a source of flux throughout the ABL even in the entrainment layer where it is known to act as a sink for uniformly emitted scalars (for instance see Fig. 7a in Vinuesa and Galmarini (2007) where the same scaling approach is used). Over the sub-domain D, the contributions are more important when the emission is non-uniform.…”
Section: Tracer Fluxesmentioning
confidence: 97%